Meningococcal disease and vaccination in college students - Sarah Schaffer DeRoo; Rachel G. Torres; Linda Y. Fu (Taylor & Francis Group, 2021)
Neisseria meningitidis is a bacterial pathogen capable of causing rapidly progressing illness from nonspecific symptoms to end-organ failure or death in a matter of hours to days. Despite the availability of meningococcal vaccines, there remains a notable disease incidence peak among individuals aged 18-19 years, with college students at increased risk for disease relative to non-college students. Between 2007 and 2017, as many as one in five colleges in the United States experienced an outbreak of meningococcal disease at their own or a nearby institution. Evidence-based strategies to promote meningococcal vaccination among students can be adapted for the college setting, but barriers exist that limit widespread implementation of these strategies by colleges. In this article, we review meningococcal disease characteristics and epidemiology among US college students, vaccination indications and coverage levels among US college students, as well as college vaccination policies and practices that can impact students' vaccine uptake.